Strategic Planning Pemimpin Pendidikan Berbasis Teologis, Filsafat, Psikologi, dan Sosiologi - Ade Zaenudin; Zarkasih Zarkasih; Endang Yuda Nuryenda; Sofyan Sauri; Faiz Karim Fatkhullah (Edulead : Journal of Education Management, 2021)
Planning is not a guarantee of success. It may be that a plan ends up failing, one of the reasons is because it is too focused on the preparation of documents, but is weak in execution or implementation. Planning is also not just an event at the beginning of an activity, but an ongoing process and will only stop when goals are achieved. There are at least two approaches to implementing strategic planning, firstly Distinctive Competence or actions taken by an institution to be able to perform activities better than its competitors, secondly Competitive Advantage, namely specific activities developed by an institution to be superior to its competitors. Strategic Planning (strategic planning) is a management tool used to manage current conditions to project conditions in the future. The urgency of strategic planning can be reviewed from various perspectives. This study tries to look at it from four perspectives, namely theological, philosophical, psychological, and sociological perspectives. Theologically Allah SWT and the prophets as educational leaders have provided examples of how to carry out strategic planning. Philosophically, humans are born as Khalifah fil ard who are given the potential to think as strategic planning capital. Psychologically, humans as educational leaders must see their students as creatures grow and develop dynamically so that strategic planning is needed to prepare it. From a sociological perspective, humans cannot be alone in leading education, there must be a collaboration with various parties and of course, this requires strategic planning so that every element involved has one vision of one goal.